Phytochemical Investigation of Insulin Plant (Costus pictus) - GEORGE, ANNIE; THANKAMMA, A.; REMA DEVI, V.K.; FERNANDEZ, ANNETTE (Asian Journal of Chemistry, 2010)
Insulin plant (Costus pictus) a folk medicine used for the treatment of diabetes mellitus is subjected to physicochemical analysis. The saponified extract is analyzed using GC-MS for the identification of the chemical constituents. 18 Chemical compounds are identified from the plant leaves.